HIV infection versus Viral Hepatitis B and C: Stigma and Discrimination experienced by HIV/AIDS patients in Public Hospitals -, Sindh Pakistan - Bughio, Nasreen Inayat (Journal of Liaquat University of Medical & Health Sciences, 2024)
Human immunodeficiency virus (HIV) impairs the immune system and causes Acquired immunodeficiency syndrome (AIDS) - an advanced stage of HIV infection. HIV/AIDS is a global health problem. To date, 43 million persons have died due to AIDS-related illnesses, and 40 million persons are living with HIV/AIDS worldwide. There is no cure, but with antiretroviral therapy (ART), HIV infection has become a manageable chronic health condition.